The Impact of COVID-19 on the Mega Sport Events: The Case of the Postponement of Olympic Games "Tokyo 2020" - Nicoliello, M. (Palgrave Studies in Cross-disciplinary Business Research, In Association with EuroMed Academy of Business, 2022)
For the first time in history the Olympic Games were postponed for a year, from 2020 to 2021. This chapter aims at analysing the impact of the crisis on the business model of the Olympic Games and what opportunities the crisis has given to the organisers to rethink the Olympics in a more sustainable way. Using the Stakeholder Theory Framework, the chapter will illustrate the consequences of the postponement on the main actors involved in the Games. This research would like to demonstrate how the crisis, initially considered a negative event, can instead prove to be an opportunity to formulate a new and more inclusive business model.